Site-Specific Clinical Behavior of the Lesions in Patients with Odontogenic Keratocyst in the Jawbone (Community Based Medical Journal, 2023)
A cross-sectional, observational study was conducted in the Department of Oral and Maxillofacial Surgery, Dhaka Dental College Hospital, Dhaka, Bangladesh, from 2014 to 2015, to assess the site-specific clinical behaviour of the lesion in patients with odontogenic keratocyst in the jawbone. The study was conducted on 25 patients who were clinically diagnosed with Odontogenic keratocyst of the jaw. Samples were selected by convenient sampling technique. Data were collected through pretested semi-structured questionnaire & analyzed by using the statistical packages of social science (SPSS) version 25.0. The mean age of the total 25 patients was 23.56± SD years and ranges from 10 to 50 years. The highest proportions of patients (44%) were from less than 20 years of age and a few (8%) of them were from more than 41 years. The study showed that 80% were male and 20% were female. In most of the cases (64%), the tooth was present in the series. Among the patients, the majority (84%) had an absence of syndrome, history of absence of tooth displacement was found 66% and absence of root resorption was 80%. Most of the keratocyts (36%) were in body and angle of the mandible, second most (24%) site was in the body of the Mandible. The knowledge about the clinical presentation of odontogenic keratocyst is needed for accurate diagnosis and prognostic assessment.CBMJ 2023 January: Vol. 12 No. 01 P: 48-52